Characterization of the population served by the Assistance Program for Ostomy Patients - Mariana Pereira Lopes; Flaviana Maria Barros Correa; Julyana Campos Esmeraldo; Caroline Silva Bezerra Reynaldo; Fernanda da Mata Vasconcelos Silva; Isabel Cristina Ramos Vieira Santos (Universidade Federal do Ceará, 2020)
Objective: to characterize the population served by the Assistance Program for Ostomy Patients. Methods: cross-sectional study, based on data from the Assistance Program for Ostomy Patients. Population of 852 registered patients. A form containing sociodemographic and clinical variables was used. Data analyzed by average comparison, using Student's 't' test and analysis of variance. Results: the age group most exposed to the investigated surgical procedure was adult/elderly (93.0%), male (52.5%). Congenital malformations and neoplasms were the main causes of ostomy for the group of children and adults/elderly, respectively. Conclusion: the age group most exposed to the studied procedure was adult/elderly, male and from the metropolitan region of the investigated state. Among children, congenital malformations required the making of a temporary ileostomy; among adults/elderly, the neoplasm corresponded to the most frequent indication of permanent colostomies.